Resolusi Konflik terhadap Penyelesaian Problematika Keluarga Perspektif Hukum Keluarga Islam - Mahmudi, Muhammad Aly; Jauhari, Ma'sum; Musthofa, Moh. Aqil; Khuluq, Moh. Sahlul (Al-Faruq: Jurnal Hukum Ekonomi Syariah dan Hukum Islam, 2023)
Conflict in a household must occur in the course of the family. In Islam conflict resolution has been accommodated with several discussions. In this study tries to reveal how the form of family conflict resolution in Islam, especially in the realm of nusyūz. This research uses qualitative methods using library research. The results of this study are, First; family conflict in Islamic jurisprudence when there is a neglect of the rights of husband and wife is called nusyūz. Second; the form of nusyūz is not only imposed on the wife but sometimes occurs on the husband who does not perform his obligations. Third; in Islam the breakdown of family relationships is not the last solution, but there are procedures that are used as alternatives so that family relationships do not end up empowering ḥakamain.